Numerical Analysis on the Effect of Hydrogen as Low-Reactivity Fuel in a 3D Scanned Engine Model Operated on RCCI Mode - Altun, Sehmus; Firat, Mujdat; Okcu, Mutlu (Springer Heidelberg, 2023)
The use of hydrogen can be a potential solution to reduce high CO and unburnt HC emissions, which is one of the most critical challenges, from Reactivity Controlled Compression Ignition (RCCI) engines at low loads as it is a very clean and carbon-free fuel candidate for internal combustion engines. Therefore, the aim of this study is designed to investigate numerically the effect of the hydrogen share on combustion characteristics in a diesel research engine operated in RCCI mode. The engine is fueled with conventional diesel and iso-octane enriched with hydrogen and is operated at 20% of the maximum torque (low load) and 2400 rpm. A 40% of conventional diesel (in the case of conventional diesel mode (CDM), its share was 100%) is injected per cycle into cylinder of the engine, while varying proportions of iso-octane (60% to 12%) and hydrogen (0% to 48%) are sprayed into the air from the intake manifold. Both CDM and RCCI combustion models built by 3D scanning of the existing engine using reverse engineering to computational fluid dynamic (CFD) was simulated through ANSYS-Forte coupled with a chemical kinetics solver (Chemkin-Pro). The simulation results showed that by adding hydrogen to iso-octane in RCCI mode, the proportion of hydrogen could be increased up to 48% while improving thermal efficiency by 33.3% in comparison with 24.9% with RCCI without hydrogen addition. Therefore, the overall hydrocarbon fuel consumption per cycle was reduced by up to 47.52%. Hydrogen addition resulted in a higher concentration of OH species in the flame front, and higher pressure and temperature in the cylinder, in turn, contributed to an increase in NOx emissions considerably but led to decrease in CO/HC emissions of RCCI operation. The decrease in the emissions of CO, HC, and C2H2 of up to 64.6, 81.8, and 76.6%, respectively, was observed by using 48% of H-2 in RCCI mode compared to RCCI mode without hydrogen addition. It was concluded that high CO and unburned HC emissions from RCCI combustion. This research provides promising contributions to the literature for using hydrogen in substitution of hydrocarbon fuels and reducing emissions from RCCI engines.
Keywords: Hydrogen; RCCI engine; Combustion; CFD; Emissions